Analysis of the Influence of Sharia Economic Literacy on Students' Interest in Using Sharia Financial Products - Firayani Firayani (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the influence of Islamic economic literacy on students' interest in using Islamic financial products. Using a quantitative approach through an explanatory survey method, this study involved 400 active students from various public and private universities in Bandung, West Java. The research instrument consists of a structured questionnaire that measures Islamic economic literacy through three main dimensions: basic Islamic knowledge, knowledge of Islamic financial products, and the application of Islamic economics in daily life. Meanwhile, the variable of interest in using Islamic financial products was measured through the dimensions of behavioral intention, attitude towards Islamic products, and supporting factors. The results of the study indicate that Islamic economic literacy has a positive and significant influence on students' interest in using Islamic financial products, with a coefficient of determination (R²) of 0.742, indicating that 74.2% of the variation in students' interest can be explained by Islamic economic literacy. This finding indicates that increasing students' understanding of Islamic principles, Islamic financial products, and their application in daily life significantly increases their interest in using Islamic-based financial services. This study provides an important contribution to the development of Islamic financial education strategies among students and the formulation of policies that support the improvement of Islamic economic literacy in efforts to expand the adoption of Islamic financial products in Indonesia.